Photoacoustic microscopy reveals the hemodynamic basis of sphingosine 1-phosphate-induced neuroprotection against ischemic stroke - Cao, Rui (Theranostics, 2018)
Rationale: Emerging evidence has suggested that sphingosine 1-phosphate (S1P), a bioactive metabolite of sphingolipids, may play an important role in the pathophysiological processes of cerebral hypoxia and ischemia. However, the influence of S1P on cerebral hemodynamics and metabolism remains unclear. Material and Methods: Uniquely capable of high-resolution, label-free, and comprehensive imaging of hemodynamics and oxygen metabolism in the mouse brain without the influence of general anesthesia, our newly developed head-restrained multi-parametric photoacoustic microscopy (PAM) is well suited for this mechanistic study. Here, combining the cutting-edge PAM and a selective inhibitor of sphingosine kinase 2 (SphK2) that can increase the blood S1P level, we investigated the role of S1P in cerebral oxygen supply-demand and its neuroprotective effects on global brain hypoxia induced by nitrogen gas inhalation and focal brain ischemia induced by transient middle cerebral artery occlusion (tMCAO). Results: Inhibition of SphK2, which increased the blood S1P, resulted in the elevation of both arterial and venous sO(2) in the hypoxic mouse brain, while the cerebral blood flow remained unchanged. As a result, it gradually and significantly reduced the metabolic rate of oxygen. Furthermore, pre-treatment of the mice subject to tMCAO with the SphK2 inhibitor led to decreased infarct volume, improved motor function, and reduced neurological deficit, compared to the control treatment with a less potent R-enantiomer. In contrast, post-treatment with the inhibitor showed no improvement in the stroke outcomes. The failure for the post-treatment to induce neuroprotection was likely due to the relatively slow hemodynamic responses to the SphK2 inhibitor-evoked S1P intervention, which did not take effect before the brain injury was induced. Conclusions: Our results reveal that elevated blood S1P significantly changes cerebral hemodynamics and oxygen metabolism under hypoxia but not normoxia. The improved blood oxygenation and reduced oxygen demand in the hypoxic brain may underlie the neuroprotective effect of S1P against ischemic stroke.